Her part to play : a novel - Erlingsson, Jenny (Revell, a division of Baker Publishing Group, 2024)
"Desperate for extra income, Adanne accepts a last-minute job as a makeup artist for a movie that's filming in her small Alabama hometown. But the money hardly seems worth having to face the actor who got her fired from her last job in Hollywood. Sparks fly on and off the set, but will either of them follow the pull of their hearts?"--